Licochalcone B suppresses oxidative stress and apoptosis accompanied by upregulating Nrf2/HO-1 pathway to ameliorate diabetic nephropathy in mice - Luo, Shan; Lan, Yake; Zhang, Ruoqi; Luan, Zhongqiu (Frontiers in Pharmacology, 2026)
IntroductionDiabetic nephropathy (DN), as a complication of diabetes, is one of the major causes of end-stage renal disease. Licochalcone B (LCB), a flavonoid active component derived from licorice, is well known for its anti-inflammatory and antioxidant properties. However, the influence of LCB on DN remains unclear. This research investigated the effect of LCB on DN and elucidated the regulatory mechanism.MethodsWe employed male C57BL/6 mice to construct a DN mouse model induced by a high-fat diet (HFD)/streptozotocin (STZ). In vitro, a high glucose (HG)-induced injury model in HK-2 (human renal tubular epithelial) cells was used to further confirm the protective effects of LCB.ResultsLCB treatment (20 mg/kg and 40 mg/kg) decreased blood glucose levels, kidney injury, glycogen deposition, and collagen accumulation in the DN mice. Moreover, LCB at a dosage of 40 mg/kg reduced albumin, creatinine, and blood urea nitrogen levels by about 70.7%, 33.4%, and 45.6%, respectively, indicating an improvement in kidney function. In renal tissues, LCB suppressed oxidative stress and apoptosis in HFD/STZ-induced mice. Consistent with in vivo findings, LCB alleviated HG-induced oxidative stress and apoptosis in HK-2 cells. Transcriptome analysis revealed that LCB affects oxidative stress and renal function-related pathways to alleviate DN. Further mechanistic studies demonstrated that LCB treatment upregulates the expressions of heme oxygenase-1 (HO-1) and nuclear factor (erythroid-derived 2)-like 2 (Nrf2), suggesting activation of the Nrf2/HO-1 signaling pathway.ConclusionTaken together, this research demonstrates that LCB suppresses oxidative stress and apoptosis accompanied by modulating the Nrf2/HO-1 pathway to ameliorate DN, which provides a promising strategy for DN treatment.